Claude Debussy - Strobel, Heinrich (Paris Balzac, 1940)
Biographie de Claude Debussy (1862-1918), pianiste et compositeur français.
Keywords: Debussy, Claude -- 1862-1918; 19th Century (1801-1900); 20th Century (1901-2000); France; Biography